WATERPROOF BREATHABLE POLYMERIC COATINGS FOR TEXTILE: THEIR PROPERTIES AND PRODUCTION FEATURES - KOLODIY, ARTEM; PLAVAN, VIKTORIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of theoretical studies of waterproof breathable polymer coatings for textiles of various types, their characteristics and features of obtaining, to create a flexible comfortable coating with the necessary technical and external appearance for special clothing while maintaining the original properties of the fabric. It is concluded that breathable polymer coatings for textiles based on polyurethane are either microporous through which vapor passes "mechanically", or solid non-porous films, where vapour diffusion occurs molecularly through hydrophilic hydrogen groups on the polymer chain, or sometimes a combination of these two. The advantage of hydrophilic polyurethane film non-porous coatings over microporous polyurethane films is that the former have high adhesion to the textile base, high gloss, resistance to water and solvents, high vapour-permeable properties, and are also less expensive and have advantages in terms of further care (dry cleaning) and durability. Another effective way to form solid non-porous polymer coatings for textile materials is to use mixtures of polymer dispersions of different types. "Breathable" polymer hybrid coatings for textiles based on polyurethane can combine the properties of different polymers and include crosslinking agents, modifiers, in particular fluorinated polymers or hydrophobic nanoparticles, mainly organosilicon. This allows for a better combination of properties, such as strength, elasticity and chemical resistance, which makes them promising for use in the textile industry for special needs.
Keywords: breathable coatings; waterproofness; vapour permeability; polyurethanes; textile materials